Use of an aortic balloon to achieve uterine conservation in a case of placenta accreta spectrum: A case report - Helena C. Bartels; David P. Brophy; John M. Moriarty; Tony Geoghegan; Gabriela McMahon; Jennifer Donnelly; Claire Thompson; Donal J. Brennan (Elsevier, 2023)
Placenta accreta spectrum (PAS) is a rare complication of pregnancy associated with a high risk of massive haemorrhage and caesarean hysterectomy. This is a case report of abdominal aortic balloon occlusion, using intravascular ultrasound, to achieve uterine conservation in a case of severe PAS. The patient was a 34-year-old woman, G2P1, with one prior caesarean section. Antenatal imaging, consisting of transabdominal and transvaginal ultrasound, and magnetic resonance imaging, showed features of PAS. The risk of caesarean hysterectomy with PAS was explained, but the patient declared a desire to retain fertility. Following multi-disciplinary discussion, it was considered appropriate to attempt uterine conservation using en-bloc myometrial and placental resection. An elective caesarean delivery was performed at 36 weeks of gestation. An aortic balloon was inserted prior to surgery using intravascular ultrasound, which allowed for radiation-free, point-of-surgery, accurate balloon sizing, by measuring the aortic diameter, and correct placement of the balloon in the abdominal aorta below the renal vessels. Intraoperative findings confirmed PAS, and a myometrial resection was performed. There were no intraoperative complications. Estimated blood loss was 1000 mL and the patient had an uncomplicated postoperative course. This case demonstrates how the use of an intravascular intraoperative aortic balloon can facilitate uterine conservation in a case of severe PAS.